Mechanical Properties of Whey–Pectin Edible Films: The Role of Plasticizer Type - Fahrullah Fahrullah; Rabyatul Auliah; Wahid Yulianto; Baiq Rani Dewi Wulandani; Bulkaini Bulkaini; Djoko Kisworo; Sukirno Sukirno (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Whey protein has been identified as a potential film-forming material; however, its mechanical properties are limited. The objective of this study is to ascertain the impact of plasticizer type on the mechanical properties of edible films composed of whey-pectin. This study employed a completely randomized design (CRD) with three replications. The treatments consisted of three types of plasticizers, namely sorbitol, glycerol, and polyethylene glycol. The obtained data were analyzed using Analysis of Variance (ANOVA), and when significant differences were observed, Duncan’s Multiple Range Test (DMRT) was subsequently applied. The findings demonstrated that the type of plasticizer exerted a negligible influence (P > 0.05) on film thickness, which ranged from 0.15 to 0.16 mm. However, the type of plasticizer had a significant effect (P < 0.05) on tensile strength and elongation. The highest tensile strength was obtained with sorbitol, whereas the highest elongation was obtained with polyethylene glycol. The findings of this study suggest the existence of a trade-off relationship between tensile strength and elongation. Sorbitol has been demonstrated to produce a strong film, while polyethylene glycol has been shown to enhance flexibility.